2005
DOI: 10.1021/ma051551i
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design and in-Situ FTIR Analyses of Colorimetrically Reversibe Polydiacetylene Supramolecules

Abstract: The colorimetric reversibility of polydiacetylene supramolecules, derived from a variety of functionalized diacetylenic lipids, has been subjected to detailed investigation. In an earlier effort, it was shown that polydiacetylene vesicles prepared from PCDA-mBzA 1, bearing terminal m-carboxyphenylamido groups, display complete reversibility upon thermal stimulation [J. Am. Chem. Soc. 2003, 125, 8976]. The origin and nature of reversible thermochromism in these systems have been elucidated insitu in the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
175
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 198 publications
(181 citation statements)
references
References 50 publications
5
175
1
Order By: Relevance
“…Since molecular packing in crystals is determined by the intermolecular interactions between monomers, the selection of substituents attached to the butadiyne moiety is quite important in the preparation of PDAs. On the other hand, much research on the physical properties of PDAs, such as electrical, 3,4 chromic [5][6][7] and nonlinear optical (NLO) [8][9][10] properties, which originate from the p-conjugated backbone structure, have been undertaken. In particular, the third-order NLO properties of PDAs have attracted interest.…”
mentioning
confidence: 99%
“…Since molecular packing in crystals is determined by the intermolecular interactions between monomers, the selection of substituents attached to the butadiyne moiety is quite important in the preparation of PDAs. On the other hand, much research on the physical properties of PDAs, such as electrical, 3,4 chromic [5][6][7] and nonlinear optical (NLO) [8][9][10] properties, which originate from the p-conjugated backbone structure, have been undertaken. In particular, the third-order NLO properties of PDAs have attracted interest.…”
mentioning
confidence: 99%
“…[43][44][45][46][47] In addition, all the vesicles had in common a peak around 1690 cm −1 , which was due to the carbonyl groups involving hydrogen bonds. 30 The results suggested that the five polymerized vesicles had enough cohesiveness among the PCDA molecules to form hydrogen bonds between headgroups and self-assemblies between alkyl groups.…”
Section: Resultsmentioning
confidence: 95%
“…[36][37][38][39] Regarding factors affecting conformation change in the π-bond, head group interactions, arising from hydrogen bonds/lateral stacking between aromatic rings or the flexibility of head groups, were suggested to play important roles. 30,[33][34][35]40 Meanwhile, melting of the unreacted monomers was also suggested to be a factor for the conformation change of the backbone. 41 On the other hand, it is little known how deeply the characteristics of selfassembled bilayers (in case of vesicles) or films of the polydiacetylenes connected with the conformation change of the backbone, affecting the colorimetric transitions.…”
Section: -35mentioning
confidence: 99%
“…As a result, they can be readily generated in matrix formats for biosensing purposes. Finally, color (blue-to-red) and fluorescence (noneto-red) changes occur when PDAs are subjected to environmental perturbations, such as temperature and ligand-receptor interactions.[ [16][17][18][19][20][21][22][23][24] In general, PDA-based chemosensors are prepared as vesicles in aqueous solutions, [25] Langmuir-Blodgett (LB)/ Langmuir-Schaefer (LS) films, [6] or immobilized vesicles in/on solid supports. [26,27] Recently, we reported new methods for the fabrication of PDA-based microarray chips, [28] PDAembedded electrospun fiber sensors, [29] and flexible strip-type PDA sensors.…”
mentioning
confidence: 99%
“…3), derived from 10,12-pentacosadiynoic acid (PCDA) and 2,2 0 -(ethylenedioxy)bis (ethylamine) (EDEA), was subjected to the standard procedure for the formation of PDA vesicles in deionized water. [25] A typical deep-blue-colored solution was obtained when a sonicated suspension containing the monomeric diacetylene was irradiated with 254 nm UV light. Scanning electron microscopy (SEM) images reveal that the polymerized diacetylene vesicles are nearly spherical with sub-100 nm diameters (Fig.…”
mentioning
confidence: 99%